Społeczne aspekty działalności dobroczynnej Bazylego podczas klęski głodu w 369 roku - Szablewska, Elżbieta (Vox Patrum, 2010)
During the famous famine of 369 Basil, a renown priest of Caesarea, was not hesitant to take up leadership and to successfully face a severe food shortage, which posed a major threat to the inhabitants of Cappadocia. His friend, Gregory of Nazianzus, was careful to point out that Basil’s involvement in the crisis took up a form of gathering the poor, distribution of food to the needy and, far and foremost, alleviation of spiritual suffering caused by hunger of words. In dealing with the wealthy landowners who used to hide grain in their granaries and with the merchants profiteering from this food shortage all he could do was to rely on his rhetorical persuasiveness. In a few sermons (Homilies 6, 8, 9, and also, probably, 7) he issued an appeal to the rich notables to make their grain available to the poor. The vast range of his arguments involved several issues like, to mention only a few, a dignity of human person, private ownership, proper attitude to wealth as such, importance of traditional system of honors connected with the conception of civic euergetism and pagan philanthropy. Basil was eager to make his audience realize the fact that wealth was not given for pleasure but should be reasonably managed and serve as a tool to help the poor and to diminish the scale of social injustice. He also argued that the care of the poor was deeply rooted in the Christian teaching (commandment of love) and practice (observed especially in the first Christian community) and was the best way to gain eternal reward.